Modulation of cytosolic-free calcium transients by changes in intracellular calcium-buffering capacity: correlation with exocytosis and O2-production in human neutrophils (The Rockefeller University Press, 1984)
The intracellularly trapped fluorescent calcium indicator, quin 2, was used not only to monitor changes in cytosolic-free calcium, [Ca2+]i, but also to assess the role of [Ca2+]i in neutrophil function. To increase cytosolic calcium buffering, human neutrophils were loaded with various quin 2 concentrations, and [Ca2+]i transients, granule content release as well as superoxide [O2-] production were measured in response to the chemotactic peptide formyl-methionyl-leucyl- phenylalanine (fMLP) and the calcium ionophore ionomycin. Receptor- mediated cell activation induced by fMLP caused a rapid rise in [Ca2+]i. The extent of [Ca2+]i rise and granule release were inversely correlated with the intracellular concentration of quin 2, [quin 2]i. These effects of [quin 2]i were more pronounced in the absence of extracellular Ca2+. The initial rate and extent of fMLP-induced O2- production were also inhibited by [quin 2]i. The rates of increase of [Ca2+]i and granule release elicited by ionomycin were also inversely correlated with [quin 2]i in Ca2+-containing medium. As the effects of ionomycin, in contrast to those of fMLP, are sustained, the final increase in [Ca2+]i and granule release were not affected by [quin 2]i. A further reduction of fMLP effects was seen when intracellular calcium stores were depleted by incubating the cells in Ca2+-free medium with ionomycin. The specificity of quin 2 effects on cellular calcium were confirmed by loading the cells with Anis/AM, a structural analog of quin 2 with low affinity for calcium which did not inhibit granule release. In addition, functional responses to phorbol myristate acetate (PMA), which stimulates neutrophils without raising [Ca2+]i, were not affected by [quin 2]i. The findings indicate that rises in [Ca2+]i control the rate and extent of granule exocytosis and O2-generation in human neutrophils exposed to the chemotactic peptide fMLP.